2020
DOI: 10.1038/s41598-020-59269-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune protection is dependent on the gut microbiome in a lethal mouse gammaherpesviral infection

Abstract: immunopathogenesis in systemic viral infections can induce a septic state with leaky capillary syndrome, disseminated coagulopathy, and high mortality with limited treatment options. Murine gammaherpesvirus-68 (MHV-68) intraperitoneal infection is a gammaherpesvirus model for producing severe vasculitis, colitis and lethal hemorrhagic pneumonia in interferon gamma receptor-deficient (IFNγR −/−) mice. In prior work, treatment with myxomavirus-derived Serp-1 or a derivative peptide S-7 (G 305 TTASSDTAITLIPR 319)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 82 publications
0
22
0
1
Order By: Relevance
“…In more recent work, Serp-1 was found to be an effective therapeutic against severe vasculitis in both human temporal artery biopsy transplants from patients suspected to have Giant cell arteritis into SCID mice and in the lethal MHV68 gammaherpesvirus-induced vasculitis in interferon gamma receptor-deficient mice ( 162 , 209 ). Interestingly, peptides derived from Serp-1 are also therapeutically effective in the gammaherpesvirus-induced vasculitis model and protection imparted by both the full protein and the peptide derivatives are dependent on composition of the gut microbiome ( 202 , 210 , 211 ). In vitro studies demonstrated that, these reactive center loop (RCL) peptides bound and inhibited mammalian serpins ( 202 ).…”
Section: Serp-1: a Virus-derived Coagulation Regulator And Therapeutimentioning
confidence: 99%
“…In more recent work, Serp-1 was found to be an effective therapeutic against severe vasculitis in both human temporal artery biopsy transplants from patients suspected to have Giant cell arteritis into SCID mice and in the lethal MHV68 gammaherpesvirus-induced vasculitis in interferon gamma receptor-deficient mice ( 162 , 209 ). Interestingly, peptides derived from Serp-1 are also therapeutically effective in the gammaherpesvirus-induced vasculitis model and protection imparted by both the full protein and the peptide derivatives are dependent on composition of the gut microbiome ( 202 , 210 , 211 ). In vitro studies demonstrated that, these reactive center loop (RCL) peptides bound and inhibited mammalian serpins ( 202 ).…”
Section: Serp-1: a Virus-derived Coagulation Regulator And Therapeutimentioning
confidence: 99%
“…The importance of the microbiota in establishing an appropriate anti-viral immune response has been noted [16,17]. Exacerbated systemic infection by several enteric and non-enteric viruses was observed in Ab-treated mice, including vesicular stomatitis and influenza virus [18], murine gammaherpesvirus [19], respiratory syncytial virus [20], encephalomyocarditis virus [21], and West Nile, Dengue and Zika viruses [22]. In some cases, microbiota depletion has been linked to a defective innate immune response characterized by low levels of type I IFN expression (IFNb), which hampered the ability to mount an effective antiviral macrophage response [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Those microorganisms undergo dynamic changes due to numerous factors, including ageing, changes in diet, environment, or infection by pathogens [28, 4547]. Recent studies have shown that interaction between host microbiome and viruses may play a crucial role in dictating disease pathogenesis in mammalian hosts [24, 48, 49]. As in all vertebrates, chicken mucosal surfaces are share by diverse and dynamic population of microbiome [5052].…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence has shown that the gut microbiome can play a role in pathogenesis of various human diseases including those with primary involvement outside of the gut, such as respiratory, renal, or neurologic [2022]. For instance, recent studies reveal that immune protection and severity of infection by gammaherpesvirus, which can cause severe vasculitis and lethal pneumonia or respiratory syncytial virus infection of the lungs, can be dependent on the profile of the human gut microbiome [23, 24].…”
Section: Introductionmentioning
confidence: 99%